Challenging Authorship and Authority in Psychology: A Publishing Initiative - Shefer, Tammy; van Niekerk, Ashley; Duncan, Norman; de la Rey, Cheryl (PINS-Psychology in Society, 2026)
The recent publication of Contemporary issues in human development: A South African focus (1997) heralds a significant achievement for many of us in South African psychology. This is not only because it Is a useful teaching text that talks about South Africans: black people, women, young people, and others marginalised by mainstream psychological texts, but also because it constituted an empowering experience for those who participated in writing the text. The empowerment of the participants, most of whom have felt "silenced" in the corridors of psychological knowledge production, is not just an achievement for a few individuals, but represents a challenge to the dominance of white and male voices in South African psychology.